1995
DOI: 10.1080/0305569950210203
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Effects of a Staff Development Programme on Effective Instruction and Classroom Management for Teachers in Multigrade Classes

Abstract: This study describes the long-term effects of a staff development programme based on selected findings from teaching effectiveness research in schools with multigrade or mixed-age classes. The short-term effects of this programme were examined in two studies directed at schools with multigrade classes. The first improvement study was conducted in the school year 1986/87; the second improvement study was conducted in 1989/90. In the latter study, the effects of coaching in addition to participation in the staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…Based on pretraining and posttraining classroom observation, these studies revealed a significant treatment effect for the time-on-task levels of the students in the multigrade classes and for the instructional and management skills of the teachers. However, no significant differences in achievement were found between the students in classes with trained multigrade teachers and the students in classes with untrained single-grade teachers (Roelofs, 1993;Roelofs, Raemaekers, & Veenman, 1991;Roelofs, Veenman, & Raemaekers, 1994;Veenman & Raemaekers, 1995).…”
Section: Veenmanmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on pretraining and posttraining classroom observation, these studies revealed a significant treatment effect for the time-on-task levels of the students in the multigrade classes and for the instructional and management skills of the teachers. However, no significant differences in achievement were found between the students in classes with trained multigrade teachers and the students in classes with untrained single-grade teachers (Roelofs, 1993;Roelofs, Raemaekers, & Veenman, 1991;Roelofs, Veenman, & Raemaekers, 1994;Veenman & Raemaekers, 1995).…”
Section: Veenmanmentioning
confidence: 99%
“…Following this practice, four studies and one substudy excluded from the best-evidence synthesis were included in the meta-analysis. These were studies by Eames (1989) and MacDonald and Wurster (1974) that each involved only one experimental and one control teacher, training studies by Roelofs (1993) and Veenman and Raemaekers (1995), and the reading achievement part of a study by Hoen (1972) that involved incomparable samples. The data for the meta-analysis were further supplemented with three recent studies not mentioned in the best-evidence synthe sis: Pawluk (1992), Knuver (1993), and Doolaard (1996).…”
Section: A Meta-analysis Of Multigrade and Multi-age Studiesmentioning
confidence: 99%
“…The students of coached teachers also showed greater levels of time on-task. No direct relation was found between coaching and student achievement, however (Veenman & Raemaekers, 1995).…”
Section: The Effects Of Clinical Supervision or Coachingmentioning
confidence: 84%
“…Each of these explanations fall short of giving combination class teachers credit for handling, by all accounts, a highly complex and demanding learning environment that involves a wide range of students, two curriculums, two instructional presentations, two evaluation systems, and numerous scheduling and classroom management problems. Finally, we wonder just how much training combination teachers would need to improve their student achievement, given that an apparently well-developed training program used by Veenman and his colleagues (Roelofs, 1993;Roelofs, Raemaekers, & Veenman, 1991;Roelofs, Veenman, & Raemaekers, 1994;Veenman & Raemaekers, 1995) did not raise achievement above that of single-grade classes with untrained teachers.…”
Section: Explanation Of the Finding Of No Difference In Achievementmentioning
confidence: 96%